2019
DOI: 10.1515/nanoph-2018-0196
|View full text |Cite
|
Sign up to set email alerts
|

Six-fold plasmonic enhancement of thermal scavenging via CsPbBr3 anti-Stokes photoluminescence

Abstract: One-photon up-conversion, also called anti-Stokes photoluminescence (ASPL), is the process whereby photoexcited carriers scavenge thermal energy and are promoted into a higher energy excited state before emitting a photon of greater energy than initially absorbed. Here, we examine how ASPL from CsPbBr3 nanoparticles is modified by coupling with plasmonically active gold nanoparticles deposited on a substrate. Two coupling regimes are examined using confocal fluorescence microscopy: three to four Au nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Considering the fact that single crystals of Rb 2 CuCl 3 shows a 100% PLQY, and the maximum ASPL occurs at 395 nm (3.14 eV) under 520 nm (2.385 eV), using the above equation, an optical cooling efficiency of ≈32% is estimated. This value is similar to the highest values recently reported for hybrid perovskite10a,29 and all inorganic metal halides . Further detailed spectroscopic investigations including Raman spectroscopy is in progress to better understand the physical origin of the observed ASPL of Rb 2 CuCl 3 .…”
supporting
confidence: 85%
“…Considering the fact that single crystals of Rb 2 CuCl 3 shows a 100% PLQY, and the maximum ASPL occurs at 395 nm (3.14 eV) under 520 nm (2.385 eV), using the above equation, an optical cooling efficiency of ≈32% is estimated. This value is similar to the highest values recently reported for hybrid perovskite10a,29 and all inorganic metal halides . Further detailed spectroscopic investigations including Raman spectroscopy is in progress to better understand the physical origin of the observed ASPL of Rb 2 CuCl 3 .…”
supporting
confidence: 85%
“…HBA assisted ASPL has attracted growing interest in recent years due to potential application in various fields, such as photovoltaic energy conversion [50], photoluminescence bioimaging [51], thermal probes [52], optical refrigeration of solids [53][54][55][56], etc. It was shown that this type of up-conversion can take place both in inorganic materials, such as rare-earthdoped crystals [57][58][59], II-VI [60,61], InP [62], PbS [63] semiconductor quantum dots, InP and GaAs bulk semiconductors [64], inorganic perovskite nanoparticles [65][66][67], carbon nanotubes [68], and some organic dyes based on rhodamine [69], porphyrin [70], spirolactam moieties under acidic conditions [71], polymethine [72], fluorescein and oxazine [49].…”
Section: Thermal-assisted Up-conversionmentioning
confidence: 99%
“…Lead halide perovskites (LHPs) with the structure APbX 3 ( X = Cl, Br, I) are an emerging class of semiconductor materials that have gained intense attention due to their excellent optoelectronic properties. LHP colloidal nanocrystals (NCs) exhibit strong photoluminescence quantum yield (PLQY), have high defect tolerance, and possess bandgaps that are tunable across the entire visible spectral region. , These promising features have prompted significant research into the use of LHP NCs for applications in photovoltaics, , light-emitting devices, , photodetectors, , optical refrigeration, and photocatalysis. , …”
Section: Introductionmentioning
confidence: 99%